Dedekind Multiplication Semimodules - Alwan, Ahmed H.; Alhossaini, Asaad M. A. (Iraqi Journal of Science, 2020)
The aim of this paper is to introduce the concept of Dedekind semimodules and study the related concepts, such as the class of semimodules, and Dedekind multiplication semimodules . And thus study the concept of the embedding of a semimodule in another semimodule.